ANALISIS MANAJEMEN BAZNAS KAB. LIMA PULUH KOTA DALAM PENGENTASAN KEMISKINAN (STUDI MAQASHID AL-SYARIAH ZAKAT) - Anggi Aulia Desmarinda (IAIN Batusangkar, 2017)
This research was aimed at analyze BAZNAS Lima Puluh Kota regencymanagementto solvepoorness in evaluation of religious obligatory maqashid al-syariah. This research was qualitative case study by using interview and documentation as instruments. This research found that management BAZNAS Lima Puluh Kota regencynot yet reached religious obligatory maqashid al-syariah to solvepoorness. Gathering of new religious obligatory limited to religious obligatory Public Servant Of Civil and applied program still have the character of just consumptive, so that to mustahiq not yet been reached by the maqashid. BAZNAS not yet can alter status of mustahiq become muzzaki. So also with muzzaki, trust to remit religious obligatory to BAZNAS Lima Puluh Kota regency form not yet is fully proved with religious obligatory managed by BAZNAS still religious obligatory of PNS not yet reached agriculture religious obligatory, entrepreneur and others. Though religious obligatory potency very big that is Rp 66.723.320.400 every year.This research was aimed at analyze BAZNAS Lima Puluh Kota regencymanagementto solvepoorness in evaluation of religious obligatory maqashid al-syariah. This research was qualitative case study by using interview and documentation as instruments. This research found that management BAZNAS Lima Puluh Kota regencynot yet reached religious obligatory maqashid al-syariah to solvepoorness. Gathering of new religious obligatory limited to religious obligatory Public Servant Of Civil and applied program still have the character of just consumptive, so that to mustahiq not yet been reached by the maqashid. BAZNAS not yet can alter status of mustahiq become muzzaki. So also with muzzaki, trust to remit religious obligatory to BAZNAS Lima Puluh Kota regency form not yet is fully proved with religious obligatory managed by BAZNAS still religious obligatory of PNS not yet reached agriculture religious obligatory, entrepreneur and others. Though religious obligatory potency very big that is Rp 66.723.320.400 every year.